Synthesis Literature of City Marketing and Similar Concepts (Global Journal of Management and Business Research, 2017)
City marketing is a field that is practiced in all over the world; it was developed through different stages throughout the years. The purpose of this study is to review the city marketing literature and all similar disciplines, in order to understand the very beginning of the field and its development through the time. Design/Methodology/Approach: City marketing is a field that becomes, nowadays, very important to every city and territory. A link will be shown to understand the history of the city marketing through the years and its importance now.
Keywords: city marketing; city branding; place marketing; literature; review